Penerapan Diagram Kontrol Multivariate Exponentially Weighted Moving Variance (MEWMV) - Agustina Feni Baransano; Sri Wahyuningsih; Yuki Novia Nasution (EKSPONENSIAL, 2018)
Statistical Process Control based on the quality characteristics can be divided into two kinds, namely univariate control chart and multivariate control charts.This study usedMultivariate Exponentially Weighted MovingVariance Control Chart (MEWMV).PDAM Tirta Mahakam in the districts of Kutai Kartanegara is one of the regional companies engaged in the production of drinking water, which is located in Tenggarong, East Kalimantan.In the production process, PDAM Tirta Mahakam always refers to the standard which is set by the government in producing drinking water.The purpose of this study was to determine whetherwater quality characteristics of PDAM Tirta Mahakam in a controlledstate or not by using control charts MEWMV,and to know the the water process capability. From the result of research it can be concluded that by using MEWMV control chart with weight , , and , show that the condition has been statistically in control. Process capability index MCpin multivariateexplains that the process has not been capable in precision with a value of 0,896 or not meet the specifications of the company.